Plasma attenuates endothelial injury compared to crystalloids in a ventilated rat pneumosepsis model - Daan P. van den Brink; Derek J.B. Kleinveld; Chantal A. Polet; Hendrik Veltman; Joris J.T.H. Roelofs; Nina C. Weber; Nicole P. Juffermans (PLoS ONE, 2025)
Background The dysregulated immune response during sepsis involves endothelial injury, which may be augmented by infusion of clear fluids such as crystalloids. Plasma has been suggested as an alternative resuscitation fluid but it is unclear whether previously observed benefits were due to the type of fluid, or due to less volume required to restore tissue perfusion. We hypothesized that resuscitation with plasma reduces endothelial injury, inflammation, and organ injury compared to similar and higher volumes of crystalloids in a rat pneumosepsis model. Methods Rats were intratracheally inoculated with Streptococcus Pneumoniae to induce pneumosepsis. Twenty-four hours after inoculation, animals were randomized to 4 groups: healthy controls (non-resuscitated, n = 6), 10 ml/kg/hr (standard-volume, n = 11) crystalloid resuscitation, 3.33 ml/kg/hr (low-volume, n = 11) crystalloid resuscitation or 3.33 ml/kg/hr plasma resuscitation (n = 11). Plasma markers of inflammation and endothelial injury were measured. Organs were harvested for histology and wet-to-dry weight ratio determination. Results Inoculated animals developed pneumosepsis, with lower mean arterial pressures (p < 0.001) and higher lactate levels (p < 0.001) compared to healthy controls. Animals resuscitated with plasma showed a trend towards lower syndecan-1 levels compared to the standard-volume crystalloid group (82 vs 99 ng/mL, p = 0.06) and had lower levels of VCAM-1 (424 vs 592 ng/mL, p < 0.01) compared to the standard volume crystalloid group, but not when compared to the low-volume crystalloid group. Other markers of endothelial injury or inflammation were not significantly different between groups. No significant differences were observed in histologic injury scores and wet-to-dry ratios. Conclusion Plasma resuscitation modestly reduces endothelial injury compared to crystalloid resuscitation. This effect might be attributed to decreased resuscitation volumes rather than the type of fluid.